PERCEPTIONS OF LEARNERS, TEACHERS, AND THE COMMUNITY ON THE IMPACT OF MUSEUM PROGRAMS IN SUPPORTING SECONDARY SCHOOL CURRICULA IN THE FREE STATE PROVINCE: Received: 10th October 2025, Revised: 22th November 2025, Accepted: 10th December 2025, Date of Publication: 31st December 2025 - Wendy Setlalentoa; Nomvuyo Phindane; Itumeleng Phage (PUPIL: International Journal of Teaching, Education and Learning, 2025)
Museums possess significant potential to inspire, educate, and engage learners through interactive, object-based learning. However, their benefits remain underutilized in many secondary school contexts, particularly in under-resourced regions. This study investigates the perceptions of learners, teachers, and community members regarding the contribution of museum programs to secondary school curricula in the Free State Province of South Africa. Employing a qualitative approach, semi-structured interviews were conducted with science teachers and Grade 10–12 learners from ten schools in the Xhariep District, along with selected community stakeholders. Findings revealed that while museum experiences offer substantial educational value, barriers such as logistical constraints, lack of awareness, misalignment with curricula, and socio-economic challenges hinder meaningful integration. The study advocates for strategic collaboration between museums and schools, improved outreach, and tailored educational resources to enhance accessibility and curriculum alignment. This study offers insights for educators, policymakers, and museum practitioners on strengthening educational outcomes through informal learning environments.